PELATIHAN PEMBELAJARAN MENGGUNAKAN PENDEKATAN SAINTIFIK PADA KELOMPOK KERJA GURU DI KECAMATAN MEKARSARI KABUPATEN BARITO KUALA - Barsihanor Barsihanor; Abdul Hafiz (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
This training tries to help the teachers of KKG members at Mekarsari Barito KualaRegency in understanding more about the scientific approach in learning, this training involves the teachers who are members of KKG organization. The activity begins with the delivery of a matter to scientific approach and continued with simulation study using the scientific approach and closed with a question and answer activity. After the delivery of the material and simulated learning many of the participants are asked, it shows the desire from the teachers to understand the scientific approach, and from the question that they would convey to indicate the level of their understanding about the scientific approach after a given exercise is already fairly well. They are asking more about the implementation of learning using scientific approach. Implementation of training with simulations that we combine between learn while play, making many teachers interested to apply them in their respective schools.